X-Ray computed tomography for 3D analysis of gangue mineral rejection by gravity preconcentration of sulfidic gold ores. Issue 1 (2nd January 2020) - Bacchuwar, S. S.; Mkandawire, N. P.; McGrath, T.; Lin, C. L.; Miller, J. D.
ABSTRACT: Specific gravity washability curves used in the coal industry to define the theoretical gravity separation efficiency can be used in the same way for evaluation of preconcentration operations in the metal mining industry. These theoretical metal recovery/gangue rejection curves, which establish the maximum in gravity separation efficiency, can be determined from three-demensional (3D) image analysis by high resolution X-ray microtomography (HRXMT) rather than by sink-float analysis using heavy liquid fractionation. In this way, the tedious, time-consuming, and toxic use of heavy liquids for laboratory sink-float analysis is avoided. In addition to the theoretical gravity separation efficiency curves by HRXMT, further 3D particle information on mineral composition and texture is obtained, including grain size distribution. Experimental HRXMT results for two sulfidic gold ores are presented and compared to the results from dense media cyclone experiments in order to evaluate the efficiency of gangue mineral rejection.